Cenobamate as add-on therapy for drug resistant epilepsies: effectiveness, drug to drug interactions and neuropsychological impact. What have we learned from real word evidence? - Pietrafusa, Nicola; Falcicchio, Giovanni; Russo, Emilio; Lattanzi, Simona; Goffredo, Bianca; Simeoli, Raffaele; Cairoli, Sara; Corsetti, Tiziana; Roberti, Roberta; De Tommaso, Marina; Vigevano, Federico; La Neve, Angela; et al. (Frontiers in Pharmacology, 2023)
Background: Cenobamate (CNB) is an anti-seizure medication (ASM) approved in 2021 in Europe for adjunctive treatment of focal-onset seizures in adults who were not adequately controlled with at least two previous ASMs.Methods: seizure outcome, treatment-emergent adverse events, neuropsychological profile, and blood levels of CNB and concomitant ASM were analyzed in a real world setting in two different Italian epilepsy centers in the context of CNB early access program. All patients performed a general cognitive evaluation, while 32 patients underwent the administration of a battery of neuropsychological tests at baseline and 6 months after CNB treatment. We performed CNB quantification in plasma in 31 patients at different doses in the range of 100-400 mg/day (65 measures).Results: we enrolled 54 patients with a median age of 27.9 years. The mean follow-up was 10.7 months.Most (91%) completed the efficacy analysis. At last follow-up visit, a 69.5 % median seizure reduction was registered. Thirty-two patients (59.2%) had a ≥ 50% reduction of seizures that was ≥ 75% in 20 (42.0%) cases, whilst 10 (20.2%) patients were seizure-free. The most common adverse events were somnolence (53.1%), dizziness (28.1%) and diplopia (12.5%). The correlation between CNB dose and plasma concentration, revealed a significant linear correlation (r= 0.86, p<0.0001), and there was a significant difference in mean plasma concentration/dose administered ratio (C/D ratio) between patients taking or not at least one inducer (0.10 ± 0.04 [(μg/mL)/(mg/day)]; n = 47 vs 0.13 ± 0.05 [(μg/mL)/(mg/day)]; n = 18, p=0.04). CNB dose was inversely correlated (r=-0.31, p=0.02) to the C/D ratio of Carbamazepine blood levels. and positively correlated (r=0.74, p<0.0001) with an increased plasma concentration of the active Clobazam metabolite N-desmethylclobazam. General Anxiety Disorder-7 showed a significant improvement of score from baseline evaluation of 6.82 to follow-up six months evaluation of 4.53 (p=0.03).Conclusions: In this real-world study, we registered a clinically meaningful reduction in seizure frequency after CNB administration in most patients along with a good tolerability profile. CNB treatment is correlate to a reduction in symptom severity of anxiety score. Plasma levels measurements confirm that CNB acts both as 'victim' and as 'perpetrator' of drug-drug interactions.